Effects of climate change and anthropic water uses on ecosystem services provided by an Alpine river - Mauro Carolli; Davide Geneletti; Bruno Majone; Alberto Bellin; Guido Zolezzi (Environmental Research Letters, 2025)
Several Alpine river ecosystem services (ES) depend on the streamflow regime, thus they might be affected by multiple stressors such as changing climate and anthropic water uses, with still poorly investigated consequences. We focused on the supply of three ES in an Alpine river, namely habitat provision, recreational activities, and hydroelectricity production from run-of-the-river (RoR) power plants. We applied an integrated hydrological, hydraulic and habitat modeling approach to quantify the effects of climate change (CC) on these services, based on the outcomes of four regional climate models. The paper investigated the effects of water use policies such as the introduction of prescriptions for environmental flow (EF) under the same CC models. We observed that CC significantly affects the river suitability for the supply of ES at the catchment scale, while the introduction of EF releases are relevant at a more local scales (several reaches). Under future scenarios, simulated increasing abstractions for hydroelectricity production from RoR power plants have a stronger effect on white-water rafting and a relatively smaller effect on fish habitat. Quantifying the potential effects of CC and of different strategies of river flow management under these scenarios is a promising approach to support the design of long-term water resources management strategies at catchment and local level.